Situation Report: Czechoslovakia, 25 September 1987 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Slow Moves toward Reform / by Jan Obrman Private Enterprise in Czechoslovakia Draft Law on Reform of Cooperatives Released for Debate The CPCS in Search of New Blood Ecological Cooperation with the FRG / by Frank Pohl Fifty Years since the Death of T. G. Masaryk